The advantage of the three dimensional computed tomographic (3 D-CT) for ensuring accurate bone incision in sagittal split ramus osteotomy - Coen Pramono D (Dental Journal (Majalah Kedokteran Gigi), 2005)
Functional and aesthetic dysgnathia surgery requires accurate pre-surgical planning, including the surgical technique to be used related with the difference of anatomical structures amongst individuals. Programs that simulate the surgery become increasingly important. This can be mediated by using a surgical model, conventional x-rays as panoramic, cephalometric projections and another sophisticated method such as a three dimensional computed tomography (3 D-CT). A patient who had undergone double jaw surgeries with difficult anatomical landmarks was presented. In this case the mandible foramens were seen highly relatively related to the sigmoid notches. Therefore, ensuring the bone incisions in sagittal split was presumed to be difficult. A 3D-CT was made and considered to be very helpful in supporting the pre-operative diagnostic.